KAJIAN EKONOMI PADA USAHATANI PADI ORGANIK DI DESA SUMBERNGEPOH KECAMATAN LAWANG KABUPATEN MALANG - Widayanti, Sri; Yuliati, Nuriah (Jurnal Sosial Ekonomi Pertanian, 2007)
Organic farming is farming that use natural resources input. Recently, organic farming massively conducted by farmer because the demand of output is quite increase. The organic rice is the one of organic farming. The aim this research were (1) to compare and analyze both the cost structure and the income structure between organic rice and anorganic rice farm in Sumberngepoh, (2) to compare and analyze both economic and technic efficiency in  organic and anorganic rice farm in Sumberngepoh. The analyze method that used in this research is multiple linear regression by Cobb-Douglass approach. The research location is in Sumberngepoh, Lawang-malang is basedon that place is a cultivation area and also for central of organic rice development in Malang.  The result shows that In Sumberngepoh, the farming is started from seed selection which is good and filled out, seedling, planting, and treatment which consist of irrigation, weeding, manuring and controlling the pest and disease following the organic agriculture rules. Organic rice farming is more profitable and more efficient on technical than anorganic rice farming, the functional result of Cobb-Douglas production is gotten the organic rice efficiency index  as large as 360,68 and anorganic rice farming intercept as 153,121. Based on B/C ratio result is know that B/C ratio value of organic rice farm is 2,79 and anorganic rice farm is 2,42 Key words: organic rice, economic  efficiency and technic efficiency.